2007
DOI: 10.1111/j.1600-0501.2007.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐osseointegration on rough implant surfaces previously coated with bacterial biofilm: an experimental study in the dog

Abstract: The results demonstrate that rough surfaces, which were plaque contaminated and cleaned by different methods, can re-osseointegrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 15 publications
3
62
0
18
Order By: Relevance
“…By using this model, however, Alhag et al reported that several factors such as clot adhesion/stability and cellular migration/ differentiation have to be carefully considered in the healing capacity of the peri-implant defect [11]. Therefore, Kolonidis et al introduced an alternative model in Labrador dogs [12].…”
Section: Discussionmentioning
confidence: 99%
“…By using this model, however, Alhag et al reported that several factors such as clot adhesion/stability and cellular migration/ differentiation have to be carefully considered in the healing capacity of the peri-implant defect [11]. Therefore, Kolonidis et al introduced an alternative model in Labrador dogs [12].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of the effects of citric acid and 10% H 2 O 2 , Alhag et al demonstrated that rough surfaces (with an enhanced TiO 2 layer and textured surface; Nobel Biocare AB®, Gothenburg, Sweden) which were plaquecontaminated and cleaned with either solution, can re-osseointegrate (Alhag et al, 2008). H 2 O 2 can be used successfully at a concentration of 3% in the surgical treatment of periimplantitis, employing bone substitutes with, or without, resorbable membranes (RoosJansaker et al 2007a;Roos-Jansaker et al, 2007b).…”
Section: Effects Of Chemical Cleaning Agents On Titanium Implant Surfmentioning
confidence: 99%
“…Ez a réteg átjárhatatlan az oxigén és más szennyeződések számára, ezáltal korrózió-rezisztenssé válik [19]. Kis sűrűsége (4,43 g/cm 3 ; az acélnál 45%-kal könnyebb, de ugyanolyan erős) és kiemelkedő biokompatibilitása teszi a fogászati implantológia illetve az arc-, állcsont-és szájsebészet ideális anyagává.…”
Section: Bevezetésunclassified
“…Érdes Ti implantátumok felszínének (Nobel Biocare TM , Göteborg, Svédország) plakkal történő kontaminálódása után, a citromsavas és a 10%-os H 2 O 2 -os kezelés hatására, azt tapasztalták, hogy mindkét anyag esetén újból ösz-szeointegrálódtak az implantátumok [3]. A 3%-os H 2 O 2 hatásosnak bizonyult a peri-implantitisz sebészi terá-piájában is, membrán alkalmazása esetén [31,32].…”
Section: Bevezetésunclassified